2018
DOI: 10.3390/cryst8030124
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Optically Pumped Organic-Inorganic Hybrid Perovskite Amplified Spontaneous Emission via Compound Surface Plasmon Resonance

Abstract: Organic-inorganic hybrid perovskite has attracted intensive attention from researchers as the gain medium in lasing devices. However, achieving electrically driven lasing remains a significant challenge. Modifying the devices' structure to enhance the optically pumped amplified spontaneous emission (ASE) is the key issue. In this work, gold nanoparticles (Au NPs) are first doped into PEDOT: PSS buffer layer in a slab waveguide device structure: Quartz/PEDOT: PSS (with or w/o Au NPs)/CH 3 NH 3 PbBr 3 . As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Both of the one‐ and two‐photon experimental stripe is 70 µm × 6 mm pumping configuration. It has been found that the smooth surface can improve high optical gain and enhance ASE performance . Figure S9 (Supporting Information) show the AFM image of samples CsPbBr 3 ‐OA and CsPbBr 3 ‐DA QDs films.…”
Section: Resultsmentioning
confidence: 99%
“…Both of the one‐ and two‐photon experimental stripe is 70 µm × 6 mm pumping configuration. It has been found that the smooth surface can improve high optical gain and enhance ASE performance . Figure S9 (Supporting Information) show the AFM image of samples CsPbBr 3 ‐OA and CsPbBr 3 ‐DA QDs films.…”
Section: Resultsmentioning
confidence: 99%